Ethnopedagogical Technologies: Best Approaches and Practices - Arsaliev, Shavadi (Recent Patents on Computer Science, 2016)
Background: Ethno pedagogics represents a new field of education science and study the national experience and traditions of education. It is connected to ethnography, history, psychology, geography, and other social and educational sciences permitting to find out and to study national features of different regions. The national education experience can be very useful for the personality development and the cultural competences formation. Multicultural educational environment is considered to be very effective for education process. But the use of potential of national education is not effective because of the absence of methodology and theoretical base of ethno pedagogics as a science. In this paper, the basic concepts of ethno pedagogics are introduced. Ethno pedagogical Technologies are considered as a new kind of technologies connected to national education. Methods: The accurate methodological, scientific, and theoretical position in a solution of a problem of modeling of ethno pedagogical technologies allows considering the designing of ethno pedagogical process from positions of modern methodological culture. The ethno pedagogical technologies are proposed as a special set of educational operations and techniques. The ethno competence formation is considered as the global aim of ethno pedagogical technologies’ use. Results: The experimental work, described in patents, spent in educational institutions has confirmed the assumption that realization of described theoretical and methodological approaches and the purposes, strengthening of the maintenance of some humanitarian disciplines and the process of realization of ethno cultural technologies and educational activity provide effective ethno cultural formation of the person in educational space. Conclusion: The formalization of ethno pedagogical process realized in the form of technology allows revealing the most rational, objective, and valuable in the field of ethnic educational systems. It allows making educational experience the property of a bigger number of teachers. All it allows to move ahead in a solution of a problem of formation of the person capable to function successfully in the conditions of the non-uniform ethnic environment, to have high level ethno cultural competence, and also to promote the development of the theory of an ethno pedagogical science.
Keywords: ethnopedagogics